Flame retardant properties of isosorbide bis-phosphorus esters. (June 2017) - Daniel, Yoseph G.; Howell, Bob A.
Abstract: Replacements for organohalogen flame retardants, which are coming under increasing regulatory pressure worldwide, are being actively sought. Most often these are organophosphorus compounds. Organophosphorus flame retardants derived from renewable biomaterials are particularly attractive. They are independent of the supply/cost of petroleum, are often nontoxic or biodegradable and display a small carbon footprint. Starch from seed plants is currently a source of a variety of bio-derived building blocks. One of these, isosorbide, is a dihydroxy ether which may be converted to phosphorus esters. A series of such esters has been evaluated for flame retardant potential in an epoxy resin. A 1% phosphorus loading is generally sufficient to provide polymer with LOI >25 and UL 94 V1.